2007
DOI: 10.4049/jimmunol.178.11.6715
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: TLR2 Directly Triggers Th1 Effector Functions

Abstract: Toll-like receptors recognize pathogen-associated molecular patterns, activate innate immunity, and consequently modulate adaptive immunity in response to infections. TLRs are also expressed on T cells, and it has been shown that T cell activation is modulated by TLR ligands. However, the functions of TLRs on Th1 and Th2 effector cells and the molecular mechanisms underlying TLR-mediated activation are not fully understood. We analyzed TLR functions and downstream signaling events in both effector T cells. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
175
3
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 181 publications
(186 citation statements)
references
References 24 publications
4
175
3
3
Order By: Relevance
“…The present studies suggest that TLR4 signals directly drive Tc1 development in the presence of TCR or IL-12 signals. While the mechanism is still unclear and currently under investigation, this is in agreement with the previous findings that BLP preferentially promotes human and murine Th1 but not Th2 cell differentiation [7,8] and that TLR agonists selectively stimulate IFN-g but not IL-4 production by human gd T cells [9,10,12]. Our results therefore support current evidence and suggest the existence of a novel type I T-cell development pathway by directly recognising PAMP via TLRs on T cells.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…The present studies suggest that TLR4 signals directly drive Tc1 development in the presence of TCR or IL-12 signals. While the mechanism is still unclear and currently under investigation, this is in agreement with the previous findings that BLP preferentially promotes human and murine Th1 but not Th2 cell differentiation [7,8] and that TLR agonists selectively stimulate IFN-g but not IL-4 production by human gd T cells [9,10,12]. Our results therefore support current evidence and suggest the existence of a novel type I T-cell development pathway by directly recognising PAMP via TLRs on T cells.…”
supporting
confidence: 92%
“…We reported for the first time that human CD4 1 T cells express functional TLR2 and that TLR2 signals directly promote T-cell function [7]. This was subsequently confirmed in mice [8]. Furthermore, human and murine memory T cells constitutively express surface TLRs and directly recognise TLR agonists [7,9,10].…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…In addition, it has been recently shown that TLR2 mediates Th1 responses via direct stimulation of Th1 cells and via IL-12 production by APCs, and that TLR2-mediated INF-γ production is crucial for protective immunity against several infectious pathogens [71]. As Nme PorB has been shown to activate immune cells via a TLR2-mediated mechanism [31], we have examined whether the immune adjuvant effect of Nlac PorB might have a similar mechanism of action.…”
Section: Discussionmentioning
confidence: 99%